Playing with the social network: Social cohesion in resettled and non-resettled communities in Cambodia - Simone Gobien; Björn Vollan (Philipps-University Marburg, Faculty of Business Administration and Economics, 2013)
Mutual aid among villagers in developing countries is often the only means of insuring against economic shocks. We use 'lab-in-the-field experiments' in Cambodian villages to study solidarity in established and newly resettled communities. Both communities are part of a land distribution project for which participants signed up voluntarily. Playing a version of the 'solidarity game', we identify the effect of voluntary resettlement on willingness to help fellow villagers. We find that resettled players transfer on average between 45% and 75% less money than non-resettled players. The social costs of voluntary resettlement seem significantly higher than is commonly assumed.
Keywords: C93; O15; O22; R23; 330; Voluntary resettlement; Social cohesion; Risk-sharing networks; Monetary transfers; Lab-inthe-field experiment; Cambodia; Asia; Umsiedlung; Soziale Folgen; Intergenerationale Übertragung; Soziales Netzwerk; Kambodscha; Test